Performance Evaluation of Various Photovoltaic Module Technologies at Nawabshah Pakistan - Abdul Rehman Jatoi; Saleem Raza Samo; Abdul Qayoom Jakhrani (International Journal of Renewable Energy Development, 2021)
The purpose of this study was to evaluate the influence of module temperature on the efficiency of polycrystalline (p-Si), monocrystalline (m-Si), amorphous (a-Si) and thin film photovoltaic modules at outdoor environment of Nawabshah city Pakistan. The experimental setup was made and installed over the top roof of departmental building. Weather conditions, such as global solar radiation, ambient temperature, wind speed and relative humidity, power output and temperature of all selected four types of module technologies were measured at the site by logging data. Then, the logged data was normalized because of different rated power of photovoltaic modules for comparison purpose. Results revealed that less temperature impact was noted from thin film module and thus it gave more normalized power with 45.6% among other examined modules. On the basis of overall efficiency, p-Si, m-Si, a-Si and thin film modules gave 92.4%, 93.7%, 94.4% and 95.4% yearly average normalized efficiencies respectively. It was found that temperature has more impact on the efficiency of other examined modules compared to thin film modules. Thus, it is concluded from the study that thin film module is better in outdoor environment of Nawabshah